Proceedings of the 37th Conference on Design Automation - DAC '00 2000
DOI: 10.1145/337292.337545
|View full text |Cite
|
Sign up to set email alerts
|

Block placement with symmetry constraints based on the O-tree non-slicing representation

Abstract: The ordered tree (O-tree) representation has recently gained much interest in layout design automation. Different from previous topological representations of non-slicing floorplans, the O-tree representation is simpler, needs linear computation effort to generate a corresponding layout, and exhibits a smaller upper-bound of possible configurations. This paper addresses the problem of handling symmetry constraints in the context of the O-tree representation. This problem arises in analog placement, where symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 8 publications
0
62
0
Order By: Relevance
“…A B*-tree based method is proposed in [7] for handling both 1-D and 2-D symmetry constraints. Another symmetry-constrained analog placement work [8] uses O-tree representation. In [9], a symmetry-aware placement work is proposed based on Transitive Closure Graphs (TCG) data structure.…”
Section: Previous Work With Symmetry Constraintsmentioning
confidence: 99%
“…A B*-tree based method is proposed in [7] for handling both 1-D and 2-D symmetry constraints. Another symmetry-constrained analog placement work [8] uses O-tree representation. In [9], a symmetry-aware placement work is proposed based on Transitive Closure Graphs (TCG) data structure.…”
Section: Previous Work With Symmetry Constraintsmentioning
confidence: 99%
“…Balasa et al derived the symmetric-feasible conditions for several popular floorplan representations including sequence pairs (SPs) [8], O-tree [9], and binary trees [10]. To explore the solution space in the symmetric-feasible binary trees, they augmented the B * -tree [11] using various data structures, including segment trees [3], [12], red-black trees [13], and deterministic skip lists [14].…”
Section: A Previous Workmentioning
confidence: 99%
“…The solution space is much smaller in comparison with that of absolute representation, but complicated computations are needed for checking symmetry feasibility and adjusting the module positions to satisfy the constraints. Topological representations like sequencepairs [11], O-tree [4], B*-trees [3] have been applied to handle symmetry constraints in [1,12,2]. Comparisons in [2] have shown that the segment tree approach [2] has out-performed others in both solution quality and run time.…”
Section: Introductionmentioning
confidence: 99%